Analysis of risk factors related to severe postpartum hemorrhage of twin pregnancies delivered by cesarean section - Fufen Yin; Ruixue Li; Junshu Xie; Xiaohong Zhang (BMJ Publishing Group, 2022)
Objective: To investigate the risk factors of severe postpartum hemorrhage (PPH) in cesarean section of twin pregnancy, and to provide clinical basis for pregnancy management and perioperative obstetric management of twin pregnancy. Methods: The clinical data of 631 twin pregnancies with gestational age ≥28 weeks delivered by cesarean section at Peking University People's Hospital (PKUPH) from January 2004 to January 2017 were retrospectively analyzed. Methods of conception, the combined weight of twins, serum albumin level before cesarean section, operation time and other factors on the amount of blood loss during cesarean section were analyzed. Results: The proportion of severe PPH was significantly higher in in vitro fertilization-embryo transfer (IVF-ET) group, the combined weight of twins > 6000g group, serum albumin before cesarean section < 30 ​g/dl group than in the natural pregnancy group, 4000-6000g group, < 4000g group and serum albumin ≥30 ​g/dl group respectively (P ​< ​0.05). The proportion of severe PPH in the elective surgery group of twin pregnancy was higher than that in the emergency surgery group, but the difference was not statistically significant (P ​> ​0.05). Moreover, according to the surgical indications, the emergency surgery group was divided into premature rupture of membranes (PROM), labor, fetal distress and others groups, no significant difference were detected among these groups (P>0.05). Conclusion: IVF-ET, the combined weight of twins, serum albumin before operation were significantly correlated with severe PPH of twin pregnancies delivered by cesarean section, revealing that it is necessary to strengthen pregnancy management of twin pregnancy.